A New Enzyme Immunoassay for Soluble Fibrin in Plasma, with a High Discriminating Power for Thrombotic Disorders - Bos, R.; Laterveer-Vreeswijk, G. H.; Lockwood, D.; Szewczyk, K.; Nieuwenhuizen, W. (Thrombosis and Haemostasis, 1999)
Fibrin formation is a multistep process initiated by thrombin. At first thrombin converts fibrinogen to fibrin molecules which in vivo form soluble complexes with fibrinogen. Soluble fibrin is considered to be an early biochemical marker for intravascular fibrin formation and impending thrombotic events, such as deep venous thrombosis (DVT), pulmonary embolism (PE) and disseminated intravascular coagulopathy (DIC).A new enzyme immunoassay (EIA) was developed on the basis of a monoclonal antibody directed against a fibrin specific neo-epitope located on the gamma-chain of fibrinogen; γ-(312-324). In addition, it was possible to prepare a lyophilized reference material of thrombin-generated soluble fibrin, that allowed for full antigen recovery after reconstitution with buffer. Assay conditions, e.g. solid phase-Ig concentration and buffer composition, sample and conjugate dilution, and incubation times were optimised.The present assay was found to be specific (no interference of homologous antigens) and reproducible (intra-assay CV 4-8%, inter-assay CV 4-9%), and therefore highly suited for measuring soluble fibrin levels in a plasma milieu. The median normal value for soluble fibrin was determined in plasma samples obtained from apparently healthy volunteers (n = 81) and found to be 0.040 μg/ml, with a range (10-90 percentiles) of 0.026-0.059 μg/ml.A retrospective study showed that soluble fibrin levels were highly significantly increased in patients with a confirmed diagnosis of DIC (median 1.042 μg FEU/ml, range 0.160-2.319 μg/ml, n = 21, P <0.0001 vs normal), PE (median 0.527 μg FEU/ml, range 0.084-1.234 μg/ml, n = 29, P <0.0001 vs normal) and DVT (median 0.126 μg FEU/ml, range 0.059-0.878 μg/ml, n = 36, P <0.0001 vs normal), as determined by the Mann-Whitney U-Test.